LIBS Analysis of Geomaterials: Comparative Study of Basalt Plasma Induced by TEA CO2 and Nd:YAG Laser in Air at Atmospheric Pressure - Jelena Savovic; Milos Momcilovic; Sanja Zivkovic; Andrei Stancalie; Milan Trtica; Miroslav Kuzmanovic (Journal of Chemistry)
We present a study of the plasma generated by transversely excited atmospheric (TEA) CO2 laser irradiation of a basalt sample. The plasma was induced in air at atmospheric pressure. The same sample was also analyzed using a commercial LIBS system based on Nd:YAG laser and time-gated detection. The main plasma parameters, temperature, and electron number density were determined and analytical capabilities of the two systems compared. Despite differences in laser wavelength, pulse duration, applied fluence, and signal detection scheme, the two systems are comparable in terms of element detectability and limits of detection. In both cases, all elements usually present in geological samples were identified. The estimated limits of detection for most elements were below 100 ppm, while for Cu, Cr, and Sr they were around or below 10 ppm. The obtained results led to the conclusion that simple, cost-effective TEA CO2 LIBS system can find applications for geological explorations.